Psychological barriers to the use of opioid analgesics for treating pain in patients with advanced recurrent cancer (BAROC): protocol for a multicentre cohort study. Issue 3 (31st March 2022) - Tsuno, Takehiko; Fujimiya, Tatsuhiro; Kawaguchi, Takashi; Yanaizumi, Ryota; Kojima, Keiko; Miyasato, Akime; Azuma, Kanako; Saeki, Tomoya; Mawatari, Hironori; Igarashi, Takashi; Miura, Tomofumi; Ogura, Hiroyuki; et al.
Abstract : Introduction: Opioid analgesics are essential for treating cancer pain. However, patients are sometimes reluctant to use them because of concerns about addiction and dependence. Rapid pain relief following opioid administration may help overcome the psychological barriers to opioid analgesic use. This study aims to determine the relationship between psychological resistance to strong opioid analgesic use and pain amelioration speed in patients with advanced recurrent cancer. Methods and analysis: This ongoing, multicentre, observational study enrols patients aged 20 years or older with distant metastasis or advanced recurrent cancer receiving strong opioid analgesics for cancer pain for the first time. All participants, both inpatient and outpatient, were recruited from five Japanese hospitals. We are investigating the relationship between psychological barriers at the start of treatment and pain relief during the first week of treatment in these patients. The primary outcome is the Japanese version of the Barriers Questionnaire-II score at baseline. The secondary outcomes are the relationships between psychological barriers to strong opioid analgesic use and changes in pain over time. The participants are asked to fill out an electronic patient-reported outcome daily during the first week of treatment. The sample size was determined based on the number of patients in the year prior to study commencement who used strong opioid analgesics, met the eligibility criteria and could be expected to consent to participate in the study. Ethics and dissemination: The study protocol was approved by the ethics committee (approval ID B200600091) of Yokohama City University on 24 August 2020. The protocol has been reviewed by the institutional review boards at the four participating study sites. The results will be published in a peer-reviewed journal and will be presented at a relevant meeting. Trial registration number: UMIN000042443.